2006
DOI: 10.1021/bi060610x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Drives Cholesterol Out of the Ordered Lipid Bilayer Phase into the Crystal Phase in 1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine/Cholesterol/Ceramide Ternary Mixtures

Abstract: The effect of brain ceramide on the maximum solubility of cholesterol in ternary mixtures of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC), cholesterol, and ceramide was investigated at 37 degrees C by a cholesterol oxidase (COD) reaction rate assay and by optical microscopy. The COD reaction rate assay showed a sharp increase in cholesterol chemical potential as the cholesterol mole fraction approaches the solubility limit. A decline in the COD reaction rate was found after the formation of choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 44 publications
8
67
1
Order By: Relevance
“…These conclusions are consistent with reports that ceramide incorporation leads to displacement of cholesterol from ordered domains in both model membranes and cells (Ali et al, 2006;Chiantia et al, 2006Chiantia et al, , 2007Megha et al, 2006;Megha and London, 2004;Yu et al, 2005b) and with the reported ability of ceramide to substitute for cholesterol in liquid-ordered phases (Carrer et al, 2006;Silva et al, 2007). However, the correlated imaging results suggest that the membrane restructuring initiated by SMase may be more complex than simple loss of cholesterol from a ceramide-rich domain.…”
Section: Membrane Restructuringsupporting
confidence: 92%
See 1 more Smart Citation
“…These conclusions are consistent with reports that ceramide incorporation leads to displacement of cholesterol from ordered domains in both model membranes and cells (Ali et al, 2006;Chiantia et al, 2006Chiantia et al, , 2007Megha et al, 2006;Megha and London, 2004;Yu et al, 2005b) and with the reported ability of ceramide to substitute for cholesterol in liquid-ordered phases (Carrer et al, 2006;Silva et al, 2007). However, the correlated imaging results suggest that the membrane restructuring initiated by SMase may be more complex than simple loss of cholesterol from a ceramide-rich domain.…”
Section: Membrane Restructuringsupporting
confidence: 92%
“…This work has demonstrated that ceramide leads to increased membrane heterogeneity and that its effects depend on the membrane composition. Ceramide has also been shown to displace cholesterol from raft domains in model and cellular membranes (Ali et al, 2006;Chiantia et al, 2006;Megha and London, 2004;Megha et al, 2006;Yu et al, 2005b). Several recent studies have concluded that the ability of ceramide to modulate the properties of liquid-ordered domains and form ceramide-enriched gel domains is affected by the chain length and that short-chain ceramides (<C 12 ) are not good models for studies of the biological activity of ceramide (Chiantia et al, 2007;Megha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Further support for this hypothesis is the evidence that various ceramides and diglycerides not only displace cholesterol from liquid-ordered systems but also can substitute for the sterol [95,101]. Similarly, ceramide and diglyceride analogues, as well as 1-octanol, both substitute for red cell membrane cholesterol and displace it from phospholipids, as indicated by their ability to increase its sensitivity to cholesterol oxidase and the rate of its transfer to cyclodextrin [54,81].…”
Section: Agents That Displace Cholesterol From Phospholipidsmentioning
confidence: 93%
“…Surprisingly, amphipaths as disparate as 1-octanol and short-chain ceramide and diglyceride analogues also prevent lysis. Indeed, ceramides have a higher affinity than cholesterol for ordered phases of 1-palmitoyl-2-oleoyl-phosphatidylcholine [95]. It also appears that ceramides can form condensed complexes with phospholipids like sphingomyelin [96,97].…”
Section: Cholesterol Surrogatesmentioning
confidence: 99%
“…It might be related with the changed solubility of cholesterol in the micelle system. SM has been shown to facilitate the solubility of cholesterol [37] whereas formation of ceramide in bilayers may drive cholesterol from bilayer order phase to a crystal phase, thus decrease the solubility of cholesterol [38]. Further biophysical studies are required to disclose the mechanism.…”
Section: Discussionmentioning
confidence: 99%